(untitled) (Research, Society and Development, 2020)
Guazuma ulmifolia Lam., popularly known as mutamba, mutambo and mucungo, is widespread throughout Latin America. Studies on the physicochemical characteristics and the technological application of its constituents can support its use as raw material for enrichment and formulation of food products. This study aimed at to identify substances of food interest derived from mutamba fruit, through its physical, physicochemical, proximate, mineral, bioactive compounds and antioxidant activity characterization in two maturation stages. The incomplete and full physiological maturation had, on average, mass of 5.52 and 3.54 g, respectively, and acid pH of 4.84 on average. Soluble solids content increased with maturity reaching 32.9 °Brix. Regarding proximate composition, it was observed an increase in protein, lipid, crude fiber and ash; and reduction of 80% in moisture. The most concentrated minerals were K, N, Ca, P and Mg. The content of anthocyanins, polyphenols, yellow flavonoids and the antioxidant activity increased with maturation, while vitamin C remained at 1500 mg.100 g-1. This study is innovative as mutamba fruits with incomplete physiological maturation were characterized for the first time. That mutamba fruits, no matter the physiological maturation, have potential of exploitation in the food industry, due to their high content of soluble solids, as well as in the enrichment of other food products as source of vitamin C and minerals.